2020
DOI: 10.2478/bjdm-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COVID-19 relevant knowledge and attitudes of clinical and preclinical dental students in Turkey

Abstract: SummaryBackground/Aim: Dental care settings invariably carry the risk of Coronavirus Disease 2019 (COVID-19) infection because dental practice involves face-to-face communication with patients and the generation of large amounts of aerosol and droplets mixed with patients’ saliva. Since droplet and aerosol transmission are the most important concerns in dental clinics, informing future dentists about pandemic diseases at the undergraduate stage is important. In this context, the aim of this study was to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
0
13
1
3
Order By: Relevance
“…The knowledge scores of females were lower than the males, and this finding was inconsistent with the other studies [37,42]. Our study found a higher score among postgraduate students than undergraduates, because clinical students rely more on science-based resources, such as the Ministry of Health rather than social media [43]. There were significant differences found in the COVID-19 knowledge and protective behaviors among clinical and preclinical students, and the results were consistent other studies that were conducted in Turkey, China, Saudi Arabia, Italy, and Nigeria [18,30,[43][44][45][46].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The knowledge scores of females were lower than the males, and this finding was inconsistent with the other studies [37,42]. Our study found a higher score among postgraduate students than undergraduates, because clinical students rely more on science-based resources, such as the Ministry of Health rather than social media [43]. There were significant differences found in the COVID-19 knowledge and protective behaviors among clinical and preclinical students, and the results were consistent other studies that were conducted in Turkey, China, Saudi Arabia, Italy, and Nigeria [18,30,[43][44][45][46].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study found a higher score among postgraduate students than undergraduates, because clinical students rely more on science-based resources, such as the Ministry of Health rather than social media [ 43 ]. There were significant differences found in the COVID-19 knowledge and protective behaviors among clinical and preclinical students, and the results were consistent other studies that were conducted in Turkey, China, Saudi Arabia, Italy, and Nigeria [ 18 , 30 , 43 , 44 , 45 , 46 ]. The lower knowledge scores among undergraduate students highlight the need to refine the current dental curriculum, including infectious diseases epidemiology and control practices.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embrago, un estudio realizado por Labban et al (2020) discrepó con nuestra investigación y las anteriores, ya que el nivel de conocimiento es más alto en los hombres (91%) que las mujeres (87%). La mayoría de resultados…”
Section: Tabla 5 Correlación De Spearmanunclassified
“…Los datos resultantes de esta investigacion concuerdan con dos estudios; el primero desarrollado por Labban et al (2020) demostró que las personas con profesiones médicas tuvieron el 98% de respuestas correctas mientras que ajenos a las ciencias de la salud como Ciencias (87%), Economía (69%), Derecho (64%) e Ingeniería (61%) alcanzaron un puntaje menor (p< 0.05 ); así mismo un segundo estudio presentando por Peng et al (2020) evidenció que existió un mayor nivel de conocimiento en los estudiantes pertenecientes a programas médicos (83,48%) en relación a los no médicos (81,22%) (p=0.025).…”
Section: Ciencias Socialesunclassified
See 1 more Smart Citation